2018
DOI: 10.1021/acs.est.7b06133
|View full text |Cite
|
Sign up to set email alerts
|

International Trade Drives Global Resource Use: A Structural Decomposition Analysis of Raw Material Consumption from 1990–2010

Abstract: Globalization led to an immense increase of international trade and the emergence of complex global value chains. At the same time, global resource use and pressures on the environment are increasing steadily. With these two processes in parallel, the question arises whether trade contributes positively to resource efficiency, or to the contrary is further driving resource use? In this article, the socioeconomic driving forces of increasing global raw material consumption (RMC) are investigated to assess the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 72 publications
2
50
2
Order By: Relevance
“…Especially at the national level, this analysis commonly analyse how trajectories of material use relate to major phases of socioeconomic or political development, including incisive political events such as the dissolution of the Soviet Union (Krausmann et al 2016) or China's admittance to the World Trade Organisation (Velasco-Fernández et al 2015). At the country level, decomposition analyses (Muñoz and Hubacek 2008, Wenzlik et al 2015, Plank et al 2018 have identified economic growth (of absolute or per capita GDP and/or monetary final demand) as the most important driver of consumption-based measures of resource consumption. (Yu et al 2013) identified technological progress as the most important driver for China, while other drivers were found to have no significant impact on resource use (e.g.…”
Section: Comprehensive Measures Of Materials and Energy Flowsmentioning
confidence: 99%
“…Especially at the national level, this analysis commonly analyse how trajectories of material use relate to major phases of socioeconomic or political development, including incisive political events such as the dissolution of the Soviet Union (Krausmann et al 2016) or China's admittance to the World Trade Organisation (Velasco-Fernández et al 2015). At the country level, decomposition analyses (Muñoz and Hubacek 2008, Wenzlik et al 2015, Plank et al 2018 have identified economic growth (of absolute or per capita GDP and/or monetary final demand) as the most important driver of consumption-based measures of resource consumption. (Yu et al 2013) identified technological progress as the most important driver for China, while other drivers were found to have no significant impact on resource use (e.g.…”
Section: Comprehensive Measures Of Materials and Energy Flowsmentioning
confidence: 99%
“…In recent years, SDA has been widely applied to the case of environmental indicators, most notably to the issue of energy use and greenhouse gas emissions (Lenzen, ). A few studies have also investigated the drivers for changes in MFs applying an SDA approach (Munoz & Hubacek, ; Plank, Eisenmenger, Schaffartzik, & Wiedenhofer, ; Wang et al., ; Weinzettel & Kovanda, ; Wenzlik, Eisenmenger, & Schaffartzik, ). In this paper, we do not use SDA to understand the drivers of change between two points in time, but assess the drivers of MF variations calculated by a pair of two GMRIO databases for the same year (see Owen et al., for a similar study on the carbon footprint).…”
Section: Methodsmentioning
confidence: 99%
“…These approaches have tremendously increased the potential of EE-IOA for studying sustainability concerns "embodied" in consumption and displaced across supply chains. Such studies reveal structural changes in the supply chains of commodities over time and shed light on the interplay between growing consumption, international burden-shifting due to expanding supply chains and increasing industrial efficiency [92][93][94] . A recent review is 95 .…”
Section: Environmentally Extended Input-output Analysis (Ee-ioa) Focumentioning
confidence: 99%